IMPLEMENTASI NILAI-NILAI PANCASILA DALAM PEMBENTUKAN KARAKTER BAGI SISWA SISWI DI MTS SWASTA YAYASAN PENDIDIKAN ISLAM DELITUA - Muhammad Fadly; Jamiluddin Marpaung; Hotni Sari Harahap (Fakultas Agama Islam Universitas Al Washliyah, 2025)
The background to this research is because it is evident from the facts in the field, namely at the Delitua Islamic Education Foundation Private Madrasah (MTs) that you still often find some students who have not demonstrated ethics that reflect the practice of Pancasila principles. Friendly attitudes, polite behavior, responsibility, honesty, discipline and respect for others which some students still seem to lack. The formulation of the problem in this research is how to implement Pancasila values ??in character formation and the challenges of teachers in implementing Pancasila values ??in character formation for female students. This type of research is qualitative research. This research was carried out at the Delitua Islamic Education Foundation Private Mts school. The data sources in the research were school principals and teachers at the Delitua Islamic Education Foundation MTs. The instruments used in data collection were observation, interviews and documentation. The data analysis used in this research is data reduction, data presentation, and drawing conclusions. Based on the results of research at the Delitua Islamic Education Foundation Private MTs, the implementation of Pancasila values ??in character building for female students is through the habit of reading the Al-Quran (tahfidz) which is routinely carried out every day, midday prayers in congregation, getting used to always saying hello and greeting teachers, getting used to always living in cleanliness which is routinely held every day and monthly school cleanliness mutual cooperation events which are held once a month.